Verbal Ability, Argument Order, and Attitude Formation - Mozuraitis, Mindaugas; Chambers, Craig G.; Daneman, Meredyth (Frontiers in Psychology, 2016)
The current study explored the interaction of verbal ability and presentation order on readers’ attitude formation when presented with two-sided arguments. Participants read arguments for and against compulsory voting and genetic engineering, and attitudes were assessed before and after reading the passages. Participants’ verbal ability was measured combining vocabulary knowledge and reading comprehension skill. Results suggested that low verbal-ability participants were more persuaded by the most recent set of arguments whereas high verbal-ability participants formed attitudes independent of presentation order. Contrary to previous literature, individual differences in the personality trait, need for cognition, did not interact with presentation order. The results suggest that verbal ability is an important moderator of the effect of presentation order when formulating opinions from complex prose.